Les collaborations de Lucio Fontana avec Luciano Baldessari. Hypothèses pour un spatialisme de l’art et de l’architecture - Barbara Satre (In Situ)
Lucio Fontana’s work and thought fully integrate architecture at the time when, around 1950, he and Luciano Baldessari began a real collaboration. This study of the creations born from their cooperation explores the key role of architecture in Fontana’s creative process and with the architecture-sculpture principle that Baldessari adopted in his constructions during this period. The point here is to show how this encounter allowed the emergence of a singular dialectic between neo-futurism and spatialism.